Molecular Genetic Studies on Honeybees in Response to Some Environmental Stresses - Rehab Mohamed; Naglaa Ebeed; Khalid Fahmy; Naima Alsenosy; Sawsan Abdelmegeed (Arab Universities Journal of Agricultural Sciences, 2023)
The honeybee, Apis mellifera, is a widespread pollinator insect. Colony collapse disorder (CCD) has recently caused a significant decline in honeybee numbers worldwide. The beekeeping industry, agriculture, and world biodiversity are threatened by the honeybee population decline. We examined the mRNA levels of heat shock protein gene 60 (hsp60), acetylcholinesterase 1, and acetylcholinesterase 2, as biomolecular markers of the insect response to three separate forms of environmental stress, including high temperature, low temperature, and insecticide. The obtained results indicated increased levels of hsp60 and acetylcholinesterase 2 after the exposure of worker bees to temperatures of 17, 32, and 40°C for one hour, as well as exposure to a low dose of pesticide for 24 h ingestion of imidacloprid solution (2 ppm); meanwhile, acetylcholinesterase 1 showed remarkable expression decrease under heat and cold stresses but increased under pesticide treatment.  The responses of honeybees to hsp60, acetylcholinesterase 1, and acetylcholinesterase 2 are diverse and very specific to various stimuli. According to this research, the distinct expression profiles of hsp60 and acetylcholinesterase 2 can serve as useful instruments for tracking honeybees' vulnerability to varied environmental effects. Due to its insufficient responsiveness, acetylcholinesterase 1 expression is not permitted for use as a biomarker.